Creeper on the case - Mann, Greyson (Mann, Greyson. Creeper diaries, 2018)
"When Gerald's mom says he should get more "involved" at school, he joins the newspaper staff. But reporting on current events is a snooze, until he stumbles onto a few mysteries. Why is Room 117 always locked? What is the disgusting smell coming out of Mr. Zane's briefcase? And . . . why is Gerald's best friend, Sam the Slime, suddenly acting so strangely? Someone has to figure out what's really going on at Mob Middle School. But never fear--Gerald Creeper Jr., super sleuth, is here!"--Page [4] of cover.